Προπεμπτικόν (propemptikon) – żywy gatunek literacki sięgający antyku - Gaj, Beata (Colloquia Litteraria, 2022)
The article concerns a little-known and unique literary genre called propempticon, which dates back to the times of archaic Greece and the poetess Sappho. The propempticon flourished in the Hellenistic era, and then it was used wherever Mediterranean culture reached. The definitions of propempticon in different epochs are not the same, the theory of the literary gene applies to its description. Propempticon is also cultivated today in modern languages, albeit with various modifications, and an example of this can be the famous song by Andrea Bocelli under the title „Con te partirò”.